Ekonomic value added as a financial perfonmance measure and determinant of stock return - Uğuz, Handan (My University, 1998)
The mission of any business is to create value for its owners (Liggero, 1996 p.1), but; quest for value is often complicated by failure to understand how share prices are set (Stewart, 1991 p.10). Managers need to understand what creates value for shareholders and how market responds the value creating process in order to make financial decisions. Before 1950s, maximizing profits of the company was thought to be the way of creating value for the firm, but changed with MM theorems as they proved that the goal of a firm should be to maximize share price, not profits. (Liggero, 1996) Stock price of a company is therefore the most revealing indicator of the corporate performance and the maximization of the stock price is to be the primary mission of management. As all important corporate decisions should be actually analyzed in terms of how they will effect the price of the firm's stock, it is essential that managers know how stock prices are determined and what types of actions they should take to maximize its stock price. The most important question than becomes What is the engine that drives share price? (Stewart, 1991 p.21) Stock market is interested in the financial performance of a firm. Investors need a metric to determine if their investment is performing as well as industry or the whole market and to choose the right strategies for adding the most value (Liggero, 1996). Companies are therefore in search of the right performance measure that boosts the stock price and gives a better idea of whether they are creating or destroying shareholder wealth (Davies, 1996). Actually, there is a strong debate in the world of performance measures for finding the best measure determining the stock price of a company. Although there are a lot of researches, statistical studies and articles at academic level in respect of stock price predictability of performance measures like earnings, earnings per share, earnings growth, return on equity, return on assets, dividends pay out ratio; predictability power of these ratios are in question. The ambitious and unclear results of academic researches and statistical tests drive academists, analysists and corporate executives towards new searchings over corporate finance. After 1980s, a newly introduced analytical approach, named Economic Value Added, EVA, has gained an international acceptance. The primary rationale behind EVA model is that EVA is linked both theoretically and empirically to shareholder wealth and therefore to the share price of a company (Stewart, 1994). The link between EVA and stockholder wealth has been advocated by so many leading corporations around the world who have adopted EVA discipline. It's growing popularity has been reflected on Wall Street where a number of analysts studied EVA measure to evaluate stock performance of companies. (Ross, 1997) Today more than 200 major companies including Coca Cola, AT&T, Quaker Oats, CSX Corp., Briggs & Stratton Corp., Duracell, SPX Corp., Equifax, Whirlpool, have adopted EVA framework and been rewarded with significant improvements in corporate finance and stock prices. (Stewart 1991, 1994) Simply, companies that have adopted EVA discipline have similar results: increase the wealth of their owners, shareholders and value of their companies. (Ross, 1997) It is defined as being the hottest financial idea by Fortune Magazine. Theoretical framework of the research is based on testing of the hypothesis that EVA is better financial measure that comes closer than any other to capturing the true economic profit of a company. Therefore, mainly the study examines how traditional measures fail to predict stock prices and describes why EVA is far more directly linked to shareholder wealth and hence, to stock price of a company than other performance measures. Therefore, the aim of the study is twofold. Firstly, study discusses the predictability power of traditional performance measures and secondly, evaluates Economic Value Added as a performance measure and examines the correlation between EVA and stock performance, through describing characteristics and theory of EVA. This study consists of four main parts. In the first part of the study, the literature survey about the studies and valuation models from both traditional and new respect to be accomplished. For a better understanding of how share prices are set, main traditional performance measures to be discussed in the second part and the studies criticizing and supporting their predictability of stock price have been examined to demonstrate why they are in question. The third section of the study discusses EVA model, main findings about EVA in financial literature as a financial performance measure, its contribution to Market Value Added, MVA; and examines the correlation between EVA measure and the stock price. In the last section of the study, application of EVA in Turkish companies to be discussed and statistical test to be accomplished with the data from ISE (Istanbul Stock Exchange-IMKB) to test the correlation between EVA and annual returns of Turkish companies.
Keywords: İŞLETMELER-FİNANS